Penerapan Artificial Intelligence Dalam Human Resource Management Di Cafe Shelter Ground - Mutiara Dela; Prayuda Wibawa; Dani Reka Putra; Reski Valent; Vivi Nila Sari (CV. ITTC INDONESIA, 2026)
This study aims to analyze the implementation of Artificial Intelligence (AI) in Human Resource Management (HRM at Cafe Shelter Ground. The application of AI technology in human resource management is considered capable of improving efficiency, accuracy, and the quality of managerial decision-making. This research employs a qualitative approach using a case study method. Data were collected through observation, in-depth interviews with management, and documentation related to HR management processes. The findings indicate that the implementation of AI in HRM functions, particularly in recruitment, work scheduling, and employee performance evaluation, has a positive impact on work effectiveness and workforce management. However, challenges remain, including limited technological understanding and the need for system adaptation to the characteristics of a medium-scale business. Therefore, a well-planned AI implementation strategy is required to optimize the use of this technology in supporting human resource management at Cafe Shelter Ground.